Development of Practical Equipment for Heat Material for Grade VII Students of MTs Hidayatul Qomariah - Ditra Irfan Muʼārif; Rossi Delta Fitrianah; Wiji Aziz Hari Mukti (Lembaga Riset dan Inovasi Almatani, 2026)
Limited laboratory infrastructure in Islamic Junior High Schools (MTs) is a significant structural obstacle in implementing practical-based science learning. This study aims to develop simple, economical, and effective heat material practicum devices to improve the conceptual understanding of seventh-grade students at MTs Hidayatul Qomariah, Bengkulu City. The method used is research and development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The devices developed include a recycled material-based temperature measuring device, Student Worksheets (LKPD), and teacher practicum guides. Product feasibility was assessed through validation by material experts, media experts, and language experts, while its effectiveness was measured through pre-tests and post-tests on 28 seventh-grade students. The validation results showed a very high level of feasibility in all aspects: material experts (88.33%), media experts (98.33%), and language experts (89.58%). Student responses to the practicum devices reached 91.51% in the very good category. The effectiveness of learning is proven by a significant increase in the average learning outcomes from 59.29 (pre-test) to 86.89 (post-test), with an N-Gain value of 0.68 (medium category approaching high). The paired t-test produced a t-value of 11.692 which is statistically significant at the α level of 0.05 (t-table = 2.052). This finding confirms that the recycled material-based heat material practicum device is a theoretically feasible and empirically effective alternative for science learning, especially for schools operating with limited laboratory facilities.